Students' Academic Resilience During the COVID-19 Pandemic: A Literature Review - Raffa Adhira Okto Binanta; Zaenal Akbar Arrifqi; Putri Eka Prasetya Rahma Wardani; Khanaya Icha (International Journal of Studies in International Education, 2024)
This literature review explores academic resilience among students during the COVID-19 pandemic. The pandemic caused unprecedented educational disruptions, forcing students to adapt to online learning, social isolation, and increased psychological stress. Academic resilience defined as the capacity to maintain or regain academic functioning despite adversity emerged as a crucial factor in students’ adaptation. This review synthesizes findings from national and international studies published between 2020 and 2024, identifying key protective factors such as self-regulated learning, parental support, digital literacy, and school engagement. The study also discusses implications for educational policy and mental health interventions to support student well-being. The findings highlight the importance of systemic support in fostering resilience beyond individual traits.